Haiti for the Haitians by Louis-Joseph Janvier - Byrd, Brandon R.; Stieber, Chelsea (Liverpool University Press, 2023)
The world-historical significance of the Haitian Revolution is now firmly established in mainstream history. Yet Haiti's nineteenth-century has yet to receive its due, this despite independent Haiti's vital importance as the first nation to permanently ban slavery and its ongoing struggle for sovereignty in the Atlantic World. Louis-Joseph Janvier (1855-1911) is one of the foremost Haitian intellectuals and diplomats of the late-nineteenth and early twentieth centuries. His prolific oeuvre offered enduring challenges to racist slanders of Haiti and critiques of the global inequalities that arose from European colonialism and the Transatlantic Slave Trade. Through his writings, Janvier influenced the international debates about slavery, race, nation, and empire that shaped his era and, in many ways, remain unresolved today. Arguably his most powerful work, Haiti for the Haitians (1884) provides a searing critique of European and U.S. imperialism, predatory finance capitalism, and Haiti's domestic politics. It offers his vision of Haiti's future expressed through a remarkable phrase: Haiti for the Haitians. Haiti for the Haitians is the first major English translation of Janvier. Accompanied by an introduction, annotations, and an interdisciplinary collection of critical essays, this volume offers unprecedented access to this vital Haitian thinker and an important contribution to the scholarship on Haiti's nineteenth century.